Young Women's Perceptions of Traditional and Contemporary Female Beauty Ideals in China. (4th September 2018) - Jung, Jaehee
Abstract : This study examined cultural standards of the female ideal beauty as perceived by young women in China using a qualitative approach. Twenty‐three female Chinese students enrolled in Donghua University in Shanghai were recruited for focus groups. Being fat and a round face were mentioned as traditional characteristics of female beauty, while contemporary characteristics included a slim body and a small face. Women in contemporary China seem to endorse many Western standards for the female beauty ideal. These standards have been pervasive in media images in the context of rapid and disruptive social change, in particular for changing gender roles for women.